Dinamika Hukum Perikatan dalam Praktik Perbankan terhadap Perlindungan Hukum Kreditur dan Debitur - Gefira Minhatul Maula; Fahmi Firmansyah; Fariz Yohana Fatahilah (Letterlijk, 2024)
The background to this research focuses on the importance of legal protection in the relationship between creditors and debtors in banking practice. This balance of legal protection is crucial considering the potential for conflict and disputes that often occur in credit engagements. The aim of this research is to examine how legal protection is provided to creditors and debtors, as well as identifying effective dispute resolution efforts in banking practice. The research method used is a normative juridical approach with analysis of statutory regulations, legal doctrine and case studies. Data was collected through literature study and documentation relevant to the topic of legal protection and banking dispute resolution. The research results show that legal protection for creditors includes the right to collateral and guarantees, as well as a clear and firm guarantee execution mechanism. On the other hand, legal protection for debtors includes the right to transparent information, protection from abusive collection practices, and a fair debt restructuring mechanism. Further discussion reveals that efforts to resolve disputes between creditors and debtors are often carried out through mediation, arbitration and litigation. The conclusion of this research is that balanced and effective legal protection for creditors and debtors is very important to maintain stability and trust in banking practices. Increased regulation and stricter supervision, as well as the promotion of alternative dispute resolution methods, can help reduce conflict and increase compliance with existing legal regulations.